The Impact of Social Media Sites on The Patterns of Cultural Acquisition of Saudi Youth - Al-Qarni, Rahma Ahmad (Journal of Humanities & Social Sciences, 2018)
The aim of this study is to identify the impact of social media on the cultural Acquisition patterns of Saudi youth، considering them as a technical product other than the form of communication environment، which consists of cultural production and reception processes، and employing the following theoretical approaches: the theory of technological determinism، In the influence and the creation of a special cultural pattern، the theory of seeking information to interpret the behavior of the search for knowledge، and the cultural theory of monetary in order to root out the problem of social networking sites on the patterns of cultural behavior among Saudi youth، It was known about its effects on the methods of cultural achievement and patterns of thinking among Saudi youth، using the media survey methodology and applying the questionnaire tool to a sample of (700) available samples of Saudi youth. The results of the study showed the social networking site (Twitter) is the most source of knowledge contributed to the formation of culture sample study، The results show that the majority of the respondents have usually acquired reading after using the social networking site (Twitter) and increased their interest in attending cultural events and book exhibitions after following up on the cultural accounts in Twitter. The study sample gained a cultural flexibility that allowed it to follow the different opinions even those who disagree with it. The language of dialogue in the social networking site (Twitter) did not weaken the sensitivity of the study sample towards some cultural taboos such as foul language and bullying.